2022
DOI: 10.1002/lno.12197
|View full text |Cite
|
Sign up to set email alerts
|

Amazon River discharge impacts deep‐sea meiofauna

Abstract: In this study, we show that the deep‐sea meiofauna community at the Brazilian Equatorial Margin (BEM) is strongly influenced by the Amazon River. Our comparison across four deep ocean basins including Amazon, Pará‐Maranhão, Barreirinhas, and Ceará showed that the former supports a completely distinct meiofaunal community. Meiofaunal richness increased with increasing distance from the Amazon, reflecting changes in sediment proprieties among basins. Total phytopigment content at Amazon sediments was threefold h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 61 publications
1
1
0
Order By: Relevance
“…In some cases, a more linear decrease in diversity with depth (Trebukhova et al, 2013;Grzelak et al, 2017), no correlation between diversity and depth (Danovaro et al, 2009;Armenteros et al, 2022) or even an increase in diversity with depth (dos Santos et al, 2020) have been reported. Hydrodynamic regimes at local scales that regulate the food availability for meiobenthos have been discussed as one of the drivers behind this phenomenon (dos Santos et al, 2020;Pereira et al, 2022). Apart from the more linear decline in diversity and the use of Hill diversity (Hill, 1973) instead of Shannon diversity by Grzelak et al (2017), the magnitude of the decline of the different indices is comparable to our results.…”
Section: Nematode Abundance and Taxonomic Diversity Along The Bathyme...supporting
confidence: 85%
“…In some cases, a more linear decrease in diversity with depth (Trebukhova et al, 2013;Grzelak et al, 2017), no correlation between diversity and depth (Danovaro et al, 2009;Armenteros et al, 2022) or even an increase in diversity with depth (dos Santos et al, 2020) have been reported. Hydrodynamic regimes at local scales that regulate the food availability for meiobenthos have been discussed as one of the drivers behind this phenomenon (dos Santos et al, 2020;Pereira et al, 2022). Apart from the more linear decline in diversity and the use of Hill diversity (Hill, 1973) instead of Shannon diversity by Grzelak et al (2017), the magnitude of the decline of the different indices is comparable to our results.…”
Section: Nematode Abundance and Taxonomic Diversity Along The Bathyme...supporting
confidence: 85%
“…Markedly, deep‐sea ecosystems are linked to terrestrial systems. Major river sheds can significantly increase carbon input into the deep oceans (Schlünz & Schneider, 2000) affecting biodiversity (Pereira, Castellões, & Netto, 2022). The deep sea is also connected to terrestrial systems by a wooden pathway through which anthropogenic impacts on land can alter the deep oceans (McClain et al, 2016; McClain & Barry, 2014; Turner, 1973; Voight, 2007).…”
Section: Introductionmentioning
confidence: 99%